Distribución de los virus que infectan girasol en Argentina - Castellanos Collazo, Onias; Cabrera Mederos, Dariel; Trucco, Veronica Milagros; Lenardon, Sergio Luis; Giolitti, Fabian (Asociación Argentina de Fitopatólogos, 2021)
Poster